Adsorptive removal of Rhodamine B using sodium dodecyl sulfatemodified laterite soil - Thao, Pham Thu; Duc, Pham Tien (Vietnam Journal of Science and Technology, 2018)
Adsorption of the cationic dye, Rhodamine B (RhB) onto surfactant modified laterite (SML) was studied in this work. The removal efficiency of RhB using laterite increased significantly after surface modification by pre-adsorption of anionic surfactant sodium dodecyl sulfate (SDS). Some effective of parameters such as pH, adsorbent amount and ionic strength were also investigated. The optimal conditions for RhB removal using SML were found to be pH 4, adsorbent amount 0.1 g and ionic strength 0.1 mM NaCl. Under optimum conditions, RhB removal efficiency increased from 25.77% to 94.85% using SML compared without SDS modification. After 5 regenerations of SML, the removal efficiency of RhB was still higher than 90%.  Adsorption of RhB onto SML decreased with increasing NaCl concentration from 0.1 to 200 mM, demonstrating that adsorption of RhB onto SML mainly induced by electrostatic attraction. The two-step adsorption model can fit the experimental results of RhB adsorption isotherms onto SML at different NaCl concentrations. Our results indicate that SML is a novel adsorbent to remove ionic dye from aqueous solution.